DAMPAK PERISTIWA PIDATO KEMENANGAN JOE BIDEN TERHADAP ABNORMAL RETURN SAHAM PADA SUB SEKTOR LOGAM DAN MINERAL - Yumna Sekar Utami (2021)
This study is a quantitative study conducted to determine whether the events of Joe Biden's victory speech affect abnormal returns. Metals and minerals sub-sector stocks are the objects used in this research. A significance of 5% is used in this study to test the hypothesis with IBM SPSS Statistics 23 software with the different test methods of one sample t-test and paired sample t-test. The results of the study are (1) there are abnormal returns in the period before Joe Biden's victory speech, (2) there are abnormal returns in the period after Joe Biden's victory speech, and (3) there is no difference in abnormal returns before and after Joe Biden's victory speech.